Development of an Environmentally Friendly Bioplastic Film Derived from Water Hyacinth - Ankit Kumar (International Journal of Toxins and Toxics, 2024)
The water hyacinth, an invasive aquatic plant negatively impacting ecosystems, serves as a promising source for raw materials in the production of carboxymethylcellulose (CMC)-based bioplastics due to its high cellulose concentration. This initiative not only mitigates water hyacinth pollution in natural water resources but also contributes to the reduction of plastic waste through the creation of biodegradable CMC bioplastic films. The cellulose extraction from water hyacinth precedes the synthesis of CMC, followed by the production of bioplastic films. The characterization of the materials includes the use of FTIR analysis, utilizing a wavelength range of 400–4000 cm-1 to obtain the FTIR spectrum. The urgent need for increased inventions and research in this field is emphasized to overcome existing challenges and establish effective methods for producing bio-based plastics. This eco-friendly approach aims to decrease dependence on traditional polymers derived from fossil fuels, paving the way for a more sustainable future. Plastic pollution, a severe environmental issue impacting wildlife and the human food chain, particularly in areas like land, oceans, and large bodies of water, underscores the importance of transitioning towards eco-friendly alternatives.
Keywords: CMC-based bioplastic; FTIR analysis; Invasive species; sustainable plastic; water hyacinth